2015
DOI: 10.1158/1078-0432.ccr-14-2075
|View full text |Cite
|
Sign up to set email alerts
|

Bevacizumab Preconditioning Followed by Etoposide and Cisplatin Is Highly Effective in Treating Brain Metastases of Breast Cancer Progressing from Whole-Brain Radiotherapy

Abstract: Purpose: We hypothesized that a window period between bevacizumab and cytotoxic agents may enhance drug delivery into tumor tissue through bevacizumab-induced vascular normalization in patients with brain metastases of breast cancer (BMBC).Experimental Design: A single-arm phase II study was conducted in which BMBC patients refractory to whole-brain radiotherapy (WBRT) were enrolled. In a 21-day cycle, patients received bevacizumab (15 mg/kg) on day 1, which, with a 1-day window period, was followed by etoposi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(66 citation statements)
references
References 29 publications
(42 reference statements)
1
65
0
Order By: Relevance
“…In a recent preclinical mouse tumor model mimicking postsurgical adjuvant or metastatic therapy, a VEGF pathway-targeting antibody drug (bevacizumab) with chemotherapy (paclitaxel) resulted in antitumor activity in a metastatic setting [ 72 ]. Based on these data and those already mentioned, preliminary clinical studies are ongoing and have shown some efficacy in the therapeutic role of targeting VEGF in combination with chemotherapy or radiation therapy [ 32 , 73 , 74 ].…”
Section: Brain Microenvironment and Breast Cancermentioning
confidence: 99%
“…In a recent preclinical mouse tumor model mimicking postsurgical adjuvant or metastatic therapy, a VEGF pathway-targeting antibody drug (bevacizumab) with chemotherapy (paclitaxel) resulted in antitumor activity in a metastatic setting [ 72 ]. Based on these data and those already mentioned, preliminary clinical studies are ongoing and have shown some efficacy in the therapeutic role of targeting VEGF in combination with chemotherapy or radiation therapy [ 32 , 73 , 74 ].…”
Section: Brain Microenvironment and Breast Cancermentioning
confidence: 99%
“…A window period between anti-VEGF antibody bevacizumab and cytotoxic agents may enhance drug delivery to tumor tissue through bevacizumab-induced vascular normalization. In particular, administering bevacizumab 1 day earlier slightly improved the tumortargeting of etoposide and cisplatin in patients with brain metastases of breast cancer (33). The results of this study were yet limited by the lack of a control arm.…”
Section: Permeabilization-enhanced Brain Deliverymentioning
confidence: 86%
“…Selective influx of liposomes occurred at 0-8 h after injury, while the barrier closed between 8 and 24 h after injury, consistent with reports on albumin infiltration. In particular, administering bevacizumab 1 day earlier slightly improved the tumortargeting of etoposide and cisplatin in patients with brain metastases of breast cancer (33). The aforementioned strategies for BBB opening may be invasive, not specific and lack precise control over the site and timing of BBB opening, which may limit their clinical translation.…”
Section: Permeabilization-enhanced Brain Deliverymentioning
confidence: 99%
“…In patients with mycosis fungoides/Sézary syndrome, removal of immunosuppressive T reg and malignant T cells by mogamulizumab may restore the number and function of natural killer cells [13]. CCR4-expressing neoplastic T cells (fig.…”
Section: Discussionmentioning
confidence: 99%